Levels of l‐arginine and l‐citrulline in patients with erectile dysfunction of different etiology. (8th February 2017) - Barassi, A.; Corsi Romanelli, M. M.; Pezzilli, R.; Damele, C. A. L.; Vaccalluzzo, L.; Goi, G.; Papini, N.; Colpi, G. M.; Massaccesi, L.; Melzi d'Eril, G. V.
Summary: Nitric oxide is a physiologic signal essential to penile erection.l ‐citrulline (l ‐Cit) is converted intol ‐arginine (l ‐Arg), the precursor from which nitric oxide is generated. The level ofl ‐Arg andl ‐Cit in the field of male sexual function remains relatively underexplored. The aim of the study was to evaluate the level of seruml ‐Arg and ofl ‐Cit in a group of patients with erectile dysfunction. Diagnosis and severity of erectile dysfunction was based on the IIEF‐5 and its etiology was classified as arteriogenic (A‐ED), borderline (BL‐ED), and non‐arteriogenic (NA‐ED) with penile echo‐color‐Doppler in basal condition and after intracaversous injection of prostaglandin E1. Seruml ‐Arg andl ‐Cit concentrations were measured by a cation‐exchange chromatography system.l ‐Arg andl ‐Cit levels of men with A‐ED were compared with those of male with BL‐ED and NA‐ED. Median level ofl ‐Arg andl ‐Cit in 122 erectile dysfunction patients (41 A‐ED, 23 ED‐BL, 58 NA‐ED) was 82.7 and 35.4 μmol/L, respectively.l ‐Arg andl ‐Cit levels in control patients were not significantly different ( p  = 0.233 and p  = 0.561, respectively) than in total erectile dysfunction patients.l ‐Arg andl ‐Cit levels in control patients were significantly higher ( p  < 0.001 and p  < 0.018, respectively) than in A‐ED patients, but no difference ( p  > 0.50) was observed in controls and in both BL‐ED and NA‐ED patients. Patients with severe/complete‐erectile dysfunction (IIEF‐5 < 10) hadl ‐Arg orl ‐Cit level significantly lower (−17%, p  < 0.03; −13%, p  < 0.04) and were more frequent ( p  < 0.01 and p  < 0.04) under the respective median level (82.7 and 35.4 μmol/L) than those with mild‐erectile dysfunction (IIEF‐5 = 16–20).l ‐Arg andl ‐Cit levels in A‐ED were significantly lower ( p  < 0.007 and p  < 0.001, respectively) than in NA‐ED patients. Penile echo‐color‐Doppler revealed that A‐ED (peak systolic velocity ≤ 25 cm/sec) was more frequent in men withl ‐Arg under 82.7 μmol/L orl ‐Cit under 35.4 μmol/L and in the same population, the median peak systolic velocity values were lower inl ‐Arg deficient (29 vs. 35; p  < 0.04) and also inl ‐Cit deficient (31 vs. 33, p  > 0.3) but without reaching the statistical significance. Our study shows that a significant proportion of erectile dysfunction patients have lowl ‐Arg orl ‐Cit level and that this condition is more frequent in patients with arteriogenic etiology. Low levels of these nitric oxide synthase substrates might increase the erectile dysfunction risk by reducing the concentration of nitric oxide.